The Role of Spin Doctor in Political Communications to Win the Most Votes - Nur Kholisoh; As'ad As'ad (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Winning the most votes in the legislative elections is not easy, especially in areas previously controlled by the incumbents. The election-winning team, especially spin doctors, bears an effort to conduct proper political communication. The team developed also requires support including qualified political experience of its members to build a positive public image and opinion about the candidate. This study aims to investigate the role of spin doctor political communication by legislative candidates in winning the most votes in the Administrative District of Seribu Islands Regency in the 2019 election by using the theory of persuasion communication and Political Communication proposed by Dan Nimmo. This research uses a qualitative approach with a case study method. The results showed that to understand the characteristics of voters, the spin doctor mapped voters in all parts of the Administrative District of Seribu Islands Regency and conveyed political messages that were easily accepted by the public. This political message was delivered persuasively by the spin doctor team to build a positive image of one of the legislative candidates, H. Muhammad Idris, among the people of the Administrative District of Seribu Islands Regency. Positive public opinion is built through persuasive communication to constituents face-to-face with a family approach. The effort to build positive public opinion is also supported by the personality of the candidate, who is known as a generous person and likes to meet his constituents directly. This behavior makes people perceive the candidate positively and believe that the candidate has had a positive image for a long time, not only at the time of the election. The research results also indicate that building an image properly without public lies is more manageable for constituents to accept and remember.